2021
DOI: 10.21037/tlcr-21-559
|View full text |Cite
|
Sign up to set email alerts
|

Are there differences by sex in lung cancer characteristics at diagnosis? —a nationwide study

Abstract: Background: Lung cancer causes approximately 25% of all cancer deaths. Despite its relevance, few studies have analyzed differences by sex at the time of diagnosis in terms of symptoms, stage, age or smoking status.We aim to assess if there are differences between men and women on these characteristics at diagnosis. Methods:We analyzed the Thoracic Tumour Registry (TTR), sponsored by the Spanish Lung Cancer Group using a case-series design. This is a nationwide registry of lung cancer cases which started recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…In 2000, 16·5% of LCs diagnosed were SCLCs, a proportion which had fallen to 13·5% in 2010 and 12·6% in 2020. This histology spectrum was similar to that observed in the Spanish study reported by Ruano-Ravina et al 17 Notably, this trend has been noticed since the early 1980’s, 16 according to the type of tobacco use.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In 2000, 16·5% of LCs diagnosed were SCLCs, a proportion which had fallen to 13·5% in 2010 and 12·6% in 2020. This histology spectrum was similar to that observed in the Spanish study reported by Ruano-Ravina et al 17 Notably, this trend has been noticed since the early 1980’s, 16 according to the type of tobacco use.…”
Section: Discussionsupporting
confidence: 90%
“… 16 In a nationwide registry of cancer patients that is still ongoing in Spain and involving 13,590 participants, Ruano-Ravina et al reported a proportion of 25·6% women. 17 In the UK, a serial, cross-sectional, observational study derived from the National Cancer Registration and Analysis Service (NCRAS) and based on 27,795 patients suffering from LC reported a 44·4% percentage of women with a mean age of 72 years. 18 In a systematic review pertaining to gender-associated differences in fatal and non-fatal LC risk, O'Keefle and colleagues were, however, unable to identify any evidence-based difference in smoking-related LC risk among men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high percentage of stage IV diagnoses among never-smoking patients with lung cancer in our study emphasizes the importance of this understanding among physicians. As Ruano-Ravina et al point out, a large percentage of patients are asymptomatic at the time of lung cancer diagnosis, including 25% of those diagnosed with stage IV disease ( 30 ). Thus, it is critical to consider both patient and radiologic characteristics in order to guide lung nodule management and avoid missing potential diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…3 The main symptoms of lung cancer, that can occur separately or in combination, are cough, dyspnea, pain, hemoptysis, aphonia or hoarseness, weight loss or asthenia, and superior vena cava syndrome, although an asymptomatic course at the time of diagnosis is not unusual. 4 Moreover, distant metastases are frequent, especially to the central nervous system. In the early stages of NSCLC, brain metastases are present in 0.6-3% of patients 5 and this increases up to 50% in the course of the disease.…”
Section: Introductionmentioning
confidence: 99%